Macroeconomic stabilization with a common currency: Does European monetary unification create a need for fiscal insurance or federalism? - Kenneth M. Kletzer (University of Copenhagen, Economic Policy Research Unit (EPRU), 1997)
The implications of monetary unification for fiscal policies are discussed. The roles of nominal exchange rate flexibility in the presence of asymmetric national shocks and nominal price rigidities as an automatic stabilizer and source of disturbances to real economic performance are reviewed. Two main themes are considered. The first is whether a system of fiscal insurance across member states qualitatively replicates the effects of autonomous monetary policy instruments when exchange rates are permanently fixed. It is argued that while fiscal insurance schemes increase the instruments available to fiscal authorities to influence resource allocation, they do not augment existing fiscal instruments in a manner that replicates monetary policy under long run monetary neutrality in an overlapping generations economy. Restrictions imposed on national fiscal instruments as a condition of monetary unification may give rise to a need for fiscal insurance to replace their role as stabilizers. The second theme adresses whether political unification is a necessary logical conclusion of the usefulness of fiscal insurance scheme. The argument that sustainable insurance arrangements can be devised without foregoing national sovereignty over fiscal policymaking is discussed.
Keywords: 330